Revolutionizing Agriculture: Electric Tractors for Indonesian Sustainable Farming - Krisnaputra, Radhian; Aisyah, Nyayu; Hakim, Sinta Uri El; Pratiwi, Ilham Ayu Putri; Bahari, Galuh; Bahiuddin, Irfan; Sugiyanto, Sugiyanto; Hendaryanto, Ignatius Aris; Wicaksono, Dimas Aryo; Setyawan, Pendi (Proklamasi 45 University, 2024)
The global shift towards electrification has extended its reach to non-road mobile machinery, with a primary focus on agricultural applications. This growing trend reflects the larger shift towards sustainability and the minimization of environmental effects. Electric tractors and other farm machinery have gained popularity due to their environmental benefits, cost savings, and technological advancements. The electric non-road vehicles are not only quieter and more environmentally friendly but also offer the potential for reduced operational costs, making them a compelling choice for farmers looking to modernise their equipment while adhering to stringent environmental regulations. Thus, the concept of an electric tractor becomes an important topic to be discussed. This paper will discuss the development of tractors in Indonesia and proposed design for electric tractors that are suitable for Indonesia to support sustainable farming.